Effectiveness of Prevention of Narcotics Abuse in Adolescents in Ogan Komering Ilir Regency (Study at the National Narcotics in Ogan Komering Ilir Regency) - Futri, Indah Permata; Marpaung, Zailani Surya (HM Publisher, 2019)
This research is motivated by the circulation and use of narcotics in adolescents which are still rife in Ogan Komering Ilir Regency. This study aims to determine the effectiveness of prevention of drug abuse in adolescents in Ogan Komering Ilir Regency. The method used in this study is a qualitative method. Data collection techniques are done through in-depth interviews and documentation studies. The theory used in this study is the theory of open systems according to Richard M Steers, namely effectiveness can be seen based on three dimensions, namely input, process and output. Based on the results of field research shows that the input, process and output has not been effective. The conclusion of this research is that the effectiveness of prevention of narcotics abuse in adolescents in Ogan Komering Ilir Regency (study at the National Narcotics Agency Ogan komering Ilir Regency) has not been effectively implemented. This research suggests that the effectiveness of preventing narcotics abuse among adolescents (a study at the National Narcotics Agency of Ogan Komering Ilir) can run well and effectively: (1) There needs to be communication and cooperation between BNNK OKI and the Regency Government, Police and Related Agencies to help resources in the prevention of narcotics, (2) socialization activities or counselling on the dangers of anti-drugs must be increased, and (3) prioritizing the use of traditional media.